Comparison of Carbapenem-Resistant Microbial Pathogens in Combat and Non-combat Wounds of Military and Civilian Patients Seen at a Tertiary Military Hospital, Philippines (2013–2017). Issue 1 (27th June 2019) - Velasco, John Mark; Valderama, Ma Theresa; Margulieux, Katie; Diones, Paula Corazon; Peacock, Trent; Navarro, Fatima Claire; Liao, Cynthia; Chua, Domingo; Macareo, Louis; Crawford, John; Swierczewski, Brett
Abstract: Introduction: Bacterial wound infections are a danger to both military and civilian populations. The nature of injury and infection associated with combat related wounds are important in guiding antibiotic prophylaxis and empiric treatment guidelines. Materials and Methods: The isolates were screened for drug-resistance by the MicroScan Walkaway Plus System using either the Negative Breakpoint Combo Panel (NBCP) 30 or 34 or Positive Breakpoint Combo Panel (PBPC) 20 or 23. Isolates with a minimum inhibitory concentration (MIC) of ≥8 μg/mL to imipenem and/or meropenem were tested for both carbapenemase production using the CarbaNP test and real-time PCR to determine molecular resistance mechanisms. Plasmid conjugation analysis was performed to define potential for horizontal gene transfer. Results: We characterized 634 bacterial wound isolates collected from September 2013 to December 2017 from patients seen at a Philippine military tertiary hospital presenting with combat or non-combat injuries [354 (military) and 280 (civilians)]. Staphylococcus aureus was the most predominant bacterial species isolated from wounds in both populations (104/634, 16%). A variety of Gram-negative bacterial species comprised 442/634 (70%) of the isolates identified, with the most prevalent shown to be Pseudomonas aeruginosa, Enterobacter cloacae, Klebsiella pneumoniae, Escherichia coli, and Acinetobacter sp. Carbapenemase production was detected in 34/442 (8%) Gram-negative isolates. Testing for molecular resistance mechanisms showed 32/34 (17 military, 15 civilian) wound isolates were bla NDM positive and 2 were bla VIM positive, with the two bla VIM isolates found in the civilian population. Plasmid conjugation of 14 bla NDM and 2 bla VIM positive wound isolates representatives showed 2/16 (13%) produced E. coli J53 transconjugants ( E. coli from a civilian; E. cloacae from a military). Conclusion: We describe in this study the wound bacterial and antibiotic resistance profile in the military (combat vs non-combat associated) and civilian population. We observed that, with the exception of Acinetobacter sp., resistance of prevalent Gram-negative bacterial species to imipenem or meropenem were not significantly different between the military and civilian populations. We also presented data on the prevalent bacterial species isolated from both combat and non-combat wounds in a military tertiary care hospital setting as well as the carbapenemase-encoding gene primarily responsible for carbapenem resistance as well as evidence of horizontal transfer via mobile genetic elements. Clinicians may use this information to guide empiric antibiotic coverage for the predominant organisms if wound culture results are not readily available. A prospective, longitudinal evaluation of the wound bacterial profile documenting the changing bacterial flora using higher resolution molecular strategies can provide a more comprehensive understanding of the diversity, composition, and abundance of bacterial composition of the wound microbial community from the time of injury, during the course of evacuation from the field to higher level of care facilities, and up to wound resolution.